2016
DOI: 10.1007/s00392-016-0977-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of thrombophilic disorders in takotsubo patients: the (ThROmbophylia in TAkotsubo cardiomyopathy) TROTA study

Abstract: Takotsubo cardiomyopathy (TTC) pathophysiology is still unclear. A transient intracoronary thrombosis dissolved at the time of angiography has been hypothesized. We aimed to evaluate the prevalence of thrombophilic disorders in TTC patients. In 75 TTC women, 75 age- and sex-matched acute coronary syndrome (ACS) patients, both enrolled during the acute phase, and in 75 control subjects, we compared the prevalence of congenital and acquired thrombophilic alterations and the values of clotting and endothelial act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…27 Several endothelial markers, clotting activation biomarkers (von Willebrand factor and plasminogen), and lipoprotein a levels were higher in patients with TTS as compared with the healthy population, suggesting a role of endothelial dysfunction and similar pathologies contributing to the hyperviscosity of blood flow in TTS. 28 One potential explanation for the high rate of thromboembolic events in TTS compared with ACS might be due to the fact that the recovery from impaired LV function is much earlier than in the setting of an ACS. However, in the long term, the risk of thromboembolism is higher in TTS compared with ACS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Several endothelial markers, clotting activation biomarkers (von Willebrand factor and plasminogen), and lipoprotein a levels were higher in patients with TTS as compared with the healthy population, suggesting a role of endothelial dysfunction and similar pathologies contributing to the hyperviscosity of blood flow in TTS. 28 One potential explanation for the high rate of thromboembolic events in TTS compared with ACS might be due to the fact that the recovery from impaired LV function is much earlier than in the setting of an ACS. However, in the long term, the risk of thromboembolism is higher in TTS compared with ACS.…”
Section: Discussionmentioning
confidence: 99%
“…16 Even more, it has been reported that thrombus formation is a common finding in the right ventricle, especially in TTS cases with right ventricular involvement. 28 Additionally, in rare cases, tumor or thrombus formation may challenge physicians, leading to overlooking thrombus formation. 29,30 In rare cases, the use of computed tomography and cardiac magnetic resonance imaging might be required to rule out intraventricular thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…No significant alterations have been seen in thrombophilic factors in takotsubo syndrome on serology [1] and no plaque rupture has been noted on intravascular ultrasound [2]. However, Pawlowski, et al described vulnerable plaque surface, platelet activity and subsequent thrombus formation in virtual histology intravascular ultrasound evaluation of the left anterior descending coronary artery in slight or non-significant lesions [3].…”
Section: Methodology and Rationalementioning
confidence: 99%
“…Current literature has focused on the possible existence of associations between TTS and single nucleotide polymorphisms (SNPs) in genes associated with sympathetic stress. Several studies analysing polymorphisms potentially involved in the pathogenesis of TTS have been published (Table 2) [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Gwas and Polymorphism Studiesmentioning
confidence: 99%